How quantitative and qualitative of data research can be embedded together? / Norhayati Alias and Noraizah Abu Bakar - Alias, Norhayati; Abu Bakar, Noraizah (2012)
Types of research can be divided into three schools of thought: quantitative, qualitative ad mixed method. Quantitative research refers to the systematic empirical investigation of social phenomena via statistical to answer research question. As for qualitative methods, is to understand complex social phenomena such as documenting real event or studying written document. The quantitative and qualitative research can be embedded together in many forms and one form is methodology or data analysis. The benefits of embedded the perspectives, it will strengthen the reliability and validity analysis. This paper focus on data analysis technique used in mandatory disclosure of interim reporting by Malaysian companies during year 2005 and 2007.The compliance of mandatory is closures was measured using self construct disclosure checklist that go through qualitative method resulting in strengthening the reliability and validity analysis for level of compliance.